Analysis of Pathogen Characteristics and Nursing Factors of Tonsil Infection Based on Regression Equation. (11th June 2022) - Zhang, Longfang; Yang, Yuanyuan
Abstract : In order to meet the needs of the analysis and application of regression equation in clinical medicine of tonsil infection, this paper focuses on the semiparametric regression model method, cross-validation method, empirical method, and multiple regression equation analysis of atypical data using regression equation. The general method of analyzing this kind of data is given, and the parameter estimation and hypothesis testing of the model are systematically studied. The experimental results showed that among the 90 paraffin-embedded tissue specimens of chronic tonsillitis and adenoid hypertrophy in this study, 26 out of 49 male children were EBERs positive, accounting for 53.06% of male children (26/49 cases). 28 of the 41 female children were positive, accounting for 68.29 of the female children (28/41 cases). There were 14 cases in infant group, 20 cases in preschool age group, 25 cases in school-age group, and 31 cases in adolescence group; the EBERs-positive rate was 42.86% (6/14 cases) in early childhood and 55.00% in early school-age (11/20 cases), and the EBERs-positive rate was 60.00% in school-age group (15/20 cases) and 70.97% in adolescent group. The results showed that the latent infection rate of adenoid hypertrophy EBV in children with chronic tonsillitis showed no significant difference between genders. It is proved that the regression equation method can meet the needs of clinical analysis and application of tonsil infection.